Lessons from the birth of the Afrikaner and their urbanisation - Das Steÿn (Town and Regional Planning)
World history has been shaped by two significant powers, namely nationalism and imperialism. Nationalism reflects the desire of peoples to protect their own culture and forms of society. A people (nation) is not the sum of individuals, but the sum of families, clans and tribes. Imperialism is about a policy or ideology of expanding a nation's power over foreign countries, often through military force or by gaining political and economic control over other areas. The power can also be exercised by large companies such as the Dutch East India Company (VOC) which operated in the seventeenth and eighteenth centuries. They were the first large business to do business internationally and were larger than any current company such as Google or Tesla or Apple. It was independent of the Dutch government and had a navy that once surpassed that of England. Against this background, the emergence of the Afrikaner people and the striving to live freely in their own territory can be better understood. This commentary presents the birth of a people (nation) and their journey from rural farmers to urban dwellers in the twentieth century. Despite facing significant challenges, including poverty, lack of education, struggles with different governments - as people they survived irrespective of the pressure from imperialist powers.